Positive Youth Development in the Context of Climate Change: A Systematic Review - Pereira, Teresa; Freire, Teresa (Frontiers in Psychology, 2021)
Climate change has been acknowledged as one of the most significant current threats for younger generations. However, few studies have focused on climate change impacts on youth and how they can be supported. The purpose of this systematic review is to emphasize that a developmental perspective is fundamental within the interdisciplinary studies concerning climate change. Specifically, we focus our research on how the Positive Youth Development framework may inform future approaches to promote adolescents' and young adults' well-being and engagement in the context of climate change. A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The search comprised two databases, and a total of 13 articles were finally considered eligible for review. Data were analyzed using a narrative method. The results show that the Positive Youth Development theory is not yet directly embedded in existing studies concerning adolescents and young adults in the context of climate change, but some of its principles were identified. Examples are provided of how Positive Youth Development characteristics and constructs can enhance future research, practice, and policies. We highlight this framework as an innovative and promising approach in the context of climate change.